GLOBAL ANTHRAX EPIZOOTOLOGY. 3. THE INDEX OF NIDALITY - V. V. Makarov; N. Ya. Makhamat (Ветеринария сегодня)
The index of nidality is the value quantitatively characterizing the activity of the animal infection nidus and grounded on the contagiousness, which is an immanent property of a contagious disease. A detailed statistical analysis of the number of animals being exposed in anthrax nidi globally, based on ProMED and WAHIS summarized data for 2007–2017, is given in the paper. 195 anthrax nidi/outbreaks with n = 12,423 animals (64 animal per outbreak in average) and the largest range of limits from min 1 to max 2600 were taken into consideration. The highest incidence (p) of anthrax (from 27 to 7) accounts for outbreaks, where minimum animals (from 1 to 7) were exposed. The indices of anthrax nidality, which are closest to reality and calculated using statistically reliable sample of average variants (number of outbreaks, exposed animals, mortality) for basic animal species, taken as a percentage of infected animals per one outbreak in average are 11% (from 0,6 to 19) for cattle; 4% (from 1 to 20) for small ruminants; 7% (from 6 to 33) for horses.